Komunikasi Antar Pribadi Barista Dalam Menciptakan Kepuasan Pelanggan Pada Black House Purwodadi - Adi Putra, Guruh; Hindra Hastuti, Nurnawati; Sihabuddin, Sihabuddin (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Slamet Riyadi Surakarta, 2024)
Abstract Interpersonal communication is crucial in the business world, particularly in the increasingly competitive coffee shop industry. Therefore, strategies are needed to achieve specific goals, such as enhancing customer satisfaction. This study aims to analyze the interpersonal communication strategies employed by baristas to create customer satisfaction at Black House Purwodadi. The method used is field research with a qualitative descriptive approach, where data is collected through observation, interviews, and documentation. Analysis is conducted through data reduction, data presentation, and conclusion drawing, with the subjects of the study being baristas and customers. The results indicate that the interpersonal communication strategies of Black House baristas encompass several aspects: Openness, where baristas build rapport by being friendly and smiling, as well as welcoming feedback from customers; Empathy, which allows baristas to understand customer needs; and Supportive Attitude, which fosters two-way communication by listening and being open to feedback from both regular and new customers. Additionally, a Positive Attitude is demonstrated through the use of friendly language and affirming statements to appreciate customers. Equality in treatment toward all customers, regardless of appearance or age, is also prioritized to create a positive impression of the baristas' performance. Keywords: Interpersonal Communication, Barista, Customer Satisfaction